Analisis Pengaruh Kepercayaan, Kualitas Produk, dan Kemudahan Berbelanja Terhadap Keputusan Membeli bagi Pelanggan Online Shop - Muhamad Khairul Anuar (Publikasi Indonesia, 2022)
The motivation behind this research is to decide and dissect the impact of trust, quality of goods, and ease of shopping on the purchasing choices of web-based shop clients in Kasu Village, Back District, Padang. The type of exploration used in this study is